Analysis of Factors Influencing Green Innovation at PT Cahari Wasista Insani DKI Jakarta - Febrian, Wenny Desty (Greenation International Journal of Tourism and Management, 2023)
The article analysis of factors affecting green innovation at PT Cahari Wasista Insani DKI Jakarta is a literature review scientific article within the scope of management science and human resources. The purpose of this writing is to build a hypothesis of influence between variables which can later be used for further research within the scope of human resource management science. The research method used is descriptive qualitative. Data was obtained from previous studies relevant to this research and sourced from academic online media such as publish or perish, google scholar, garba digital reference and jurnal sinta. The results of this article are: 1) Use of environmentally friendly raw materials plays a role in green innovation; dan 2) Regulatory compliance plays a role in green innovation.